2011
DOI: 10.1039/c1ob05056g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of unusual glycosyl carbamates and amino acid glycosides from propargyl 1,2-orthoesters as glycosyl donors

Abstract: Propargyl 1,2-O-orthoesters are exploited for the synthesis of 1,2-trans O-glycosides of protected amino acids. N-Fmoc- and N-Cbz protected serine/threonine - benzyl/methyl esters reacted well with glucosyl-, galactosyl-, mannosyl- and lactosyl- derived propargyl 1,2-orthoesters affording respective 1,2-trans glycosides in good yields under AuBr(3)/4 Å MS Powder/CH(2)Cl(2)/rt. t-Boc serine derivative gave serine 1,2-orthoester and glycosyl carbamate. Optimized conditions enabled preparation of new glycosyl car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…16 Later, they found AuBr 3 selectively activated propargyl 1,2-orthoesters in presence of propargyl glycoside, propargyl ethers 17 and n-pentenyl glycosides. 18 Hotha and co-workers successfully applied propargyl 1,2-orthoesters in the stereoselective synthesis of 1,2-trans glycosyl amino acids 19 and interesting glycomonomers. 20 They also employed AuBr 3 -catalyzed selective activation of propargyl 1,2-orthoester in the presence of propargyl glycoside as a key step to the synthesis of tetrasaccharide motif of the Leishmania donovani lipophosphoglycan.…”
Section: Gold(iii)-catalyzed Glycosidation With Propargyl 12-orthoesmentioning
confidence: 99%
“…16 Later, they found AuBr 3 selectively activated propargyl 1,2-orthoesters in presence of propargyl glycoside, propargyl ethers 17 and n-pentenyl glycosides. 18 Hotha and co-workers successfully applied propargyl 1,2-orthoesters in the stereoselective synthesis of 1,2-trans glycosyl amino acids 19 and interesting glycomonomers. 20 They also employed AuBr 3 -catalyzed selective activation of propargyl 1,2-orthoester in the presence of propargyl glycoside as a key step to the synthesis of tetrasaccharide motif of the Leishmania donovani lipophosphoglycan.…”
Section: Gold(iii)-catalyzed Glycosidation With Propargyl 12-orthoesmentioning
confidence: 99%
“…194 It was found that the coupling of methyl glucopyranoside acceptor 59 with disarmed glucose 1,2-orthoester 195 (Scheme 13a) in presence of 10 mol% AuCl 3 provided disaccharide 197 in 65% yield with exclusive β-selectivity. To further test the limitations of this protocol, the reaction of disarmed 1,2-orthester donor 195 and propargyl glycoside acceptor 196 was investigated under the standard gold conditions (Scheme 13b), where disaccharide 198 was obtained in 72% yield as a single isomer.…”
Section: Donors With Stable Methyl and Propargyl Latent Leaving Grmentioning
confidence: 99%
“…Very recently, Hotha et al utilized 1-ethynylcyclohexyl p -nitrophenyl carbonate to synthesize alkynyl glycosyl carbonate donors from hemiacetals [19]. Also, glycocarbamates [20] obtained from glycosyl p -nitrophenyl carbonates [2124], were explored in studies of carbohydrate–protein interactions [25], ligation and surfactant properties [2627]. Although p -nitrophenyl carbonates were extensively utilized in these reactions, the nucleophilicity of amidine bases towards these carbonates was not encountered so far.…”
Section: Introductionmentioning
confidence: 99%